Kepatuhan Minum Obat Hipertensi Adalah Kunci Mengendalikan Tekanan Darah dan Mencegah Komplikasi - Rotua Elvina Pakpahan; Angelina Stefani Putri Simamora; Syukur Telaumbanua (YAYASAN PENDIDIKAN MANDIRA CENDIKIA, 2026)
Abstract Hypertension remains one of the leanding non-communicable diaseases contributing to cardiovascular morbidity and mortality worldwide. Effective blood pressure control depends not only on pharmacological therapy but also on patiens adherence to antihypertensi medication. This study aimed to review scientific evidence regarding medication adherence and its role in controlling blood pressure and preventing hypertension-related complications. This study employed a literature review approach by analyzing scientific articles published between 2020 and 2025 from Google Scholar, PubMed, and ScienceDirect databases. The reviewed studies indicate that medication adherence is significantly associated with optimal blood pressure control and reduced risk of complications such as stroke, heart failure, coronary artery disease, and chronic kidney disease. Several factors influencing adherence include patients' knowledge, motivation, family support, healthcare provider support, duration of treatment, and access to healthcare services. Continuous health education and collaborative care among patients, families, and healthcare professionals are essential to improve adherence and optimize hypertension management. Therefore, strengthening patient education and adherence interventions should become an integral part of hypertension management programs. Keywords:antihypertensive medication; blood pressure; hypertension; literature review;